Physico-chemical and sensorial characteristics evolution of vacum packaged Iberian dry-cured ham stored at refrigerated temperature - Elias, Miguel (2013)
Two groups of five dry-cured hams from Alentejano pig breed submitted to a post-salting cure of 12 months were studied. One of the groups was processed through craft methods at Barrancos (small city of south-east Alentejo region, Portugal) and the other one in a Portuguese meat plant. Equal groups of slices and unitary portions weighing about 250 g were vacuum packed and stored at 7 °C. Physico-chemical analysis (pH, aw, chlorides, total volatile basic nitrogen, thiobarbituric acid index and colour-L*, a*, b*) and sensorial evaluation (colour, off colour, aroma, off aroma, tenderness, succulence, taste, off taste, salt intensity and global evaluation) were carried out before packaging (time 0) and after 2, 5 and 8 months of storage. Statistical analysis consisted in analysis of variance considering the factors “process” (artisanal and industrial), “sample presentation” (portions and slices) and “storage time” (0, 2, 5 and 8 months). Physico-chemical analysis exhibit differences, mainly for “process” factor and sensorial evaluation for “storage time” factor. However, results evidence desirable evolution of the samples during storage time. These study allow to conclude that under refrigeration (7 °C) is possible to store vacuum packaged high quality dry-cured ham during, at least, 8 months.